Application of fuzzy-sliding mode control and electronic load emulation to the robust control of motor drives - Akpolat, Zuhtu Hakan (1999)
This thesis is concerned with the experimental investigation of robust speed control strategies for the industrial motor drive systems. The first objective of the thesis is to implement a high performance programmable dynamometer which can provide desired linear and non-linear mechanical loads for the experimental validation of the robust control methods. The discrete time implementation of the conventional dynamometer control strategy (the inverse model approach) is analysed and it is shown that this method suffers from the stability and noise problems. A new dynamometer control strategy, based on speed tracking and torque feedforward compensation, is developed and successfully implemented in the experimental system. The emulation is placed in a closed loop speed control system and the experimental results are compared with the corresponding ideal simulated results for the validation of the dynamometer control strategy. The comparisons show excellent agreement for a variety of linear and nonlinear mechanical load models and such a high performance experimental load emulation results are reported for the first time in research literature.